A novel application of contrast echocardiography to exclude active coronary perforation bleeding in patients with pericardial effusion. Issue 2 (8th November 2012) - Bagur, Rodrigo; Bernier, Mathieu; Kandzari, David E.; Karmpaliotis, Dimitri; Lembo, Nicholas J.; Rinfret, Stéphane
<x xml:space="preserve">Abstract</x> Management of hemodynamically significant cardiac tamponade will most often require pericardial drainage. In the absence of hemodynamic evidence of tamponade, however, management of a pericardial effusion represents a clinical dilemma. Pericardial leakage of blood may be transient, and extravasation may have stopped by time of echocardiographic assessment. Besides its usefulness in ischemic heart disease, contrast echocardiography might be applied in the context of coronary perforations. We report the use of contrast echocardiography in four cases of coronary perforation without overt signs of cardiac tamponade as a tool to streamline decision making as to whether perform pericardiocentesis or not. Our series demonstrate the clinical utility and effectiveness of echocardiographic contrast imaging to confirm or exclude active bleeding into the pericardial space when not otherwise visible by conventional imaging measures. © 2012 Wiley Periodicals, Inc.